A Review of Backup Mechanism for Reducing Delamination when Drilling Composite Laminates - Tsao, C.C.; Hocheng, H. (Journal of Research Updates in Polymer Science, 2016)
Over the past decades, composite materials have been increasingly utilized in various industries because of their superior mechanical properties and resistance to corrosion. Drilling is essential to produce precise holes when load-carrying structures are produced using composites. Because of the non-homogeneous and anisotropic property of composite laminates, delamination often occurs at the point where the drill exits, which affects reliability and safety. Some studies present a suppressed mechanism to prevent delamination when drilling composite laminates. The experimental results demonstrate delamination is significantly reduced by various suppressed mechanisms and greater feed rates produce the same level of delamination. The use of special drill geometries and backup has been demonstrated to be more advantageous than the use of adapted feed controls. The basis for the future development of a suppression mechanism for drilling composite laminates is determined.